Characterization of the Manufacturing Processes to Grow Triple-Junction Solar Cells. (5th May 2014) - Kalyuzhnyy, N. A.; Evstropov, V. V.; Lantratov, V. M.; Mintairov, S. A.; Mintairov, M. A.; Gudovskikh, A. S.; Luque, A.; Andreev, V. M.
Abstract : A number of important but little-investigated problems connected with III-V/Ge heterostructure in the GaInP/GaInAs/Ge multijunction solar cells grown by MOVPE are considered in the paper. The opportunity for successfully applying the combination of reflectance and reflectance anisotropy spectroscopy in situ methods for investigating III-V structure growth on a Ge substrate has been demonstrated. Photovoltaic properties of the III-V/Ge narrow-band subcell of the triple-junction solar cells have been investigated. It has been shown that there are excess currents in the Ge photovoltaic p-n junctions, and they have the tunneling or thermotunneling character. The values of the diode parameters for these current flow mechanisms have been determined. The potential barrier at the III-V/Ge interface was determined and the origin of this barrier formation during MOVPE heterogrowth was suggested.